Demographic Study of Blunt Trauma Chest in a Tertiary Care Centre in Northern Indian State of Uttar Pradesh, India - Mourya, Roopam; Pandey, S.K.; Bhartiya, S.K. (Medicine and Medical Research: New Perspectives Vol. 3, 2024)
The present study examines the demographic and epidemiological characteristics of blunt trauma chests in patients brought to the mortuary of the Department of Forensic Medicine at IMS, BHU, Varanasi for postmortem examination. The death rate from chest trauma is 10%. Falls from heights, violent falls from construction sites, falls from buildings that are still under construction, modern fast cars, lack of awareness of traffic safety rules, and poor road conditions have all contributed to a sharp rise in the prevalence. The frequency of fatalities attributable to chest injuries is increasing annually. This demonstrated the impact of preventive, social, medical, economic, and political measures in reducing the burden of thoracic trauma. Thus, knowing the problem is one of the first stages towards bringing it to light and finding a solution. This study aims to investigate the most neglected aspect of human suffering. An attempt is being made to decipher the pattern of blunt trauma to the chest and to elucidate the various causes that are responsible for the rise in instances of common blunt trauma. In this study, the epidemiology and demographic traits of 300 instances of blunt-force chest injuries are investigated. Most of them are male adults or middle-aged people between the ages of 41 and 50 who have been involved in traffic accidents. Men to women are in a ratio of 7.1:1. Most incidents took place on highways.